2005
DOI: 10.1038/sj.ijo.0803006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of perceived peer isolation and social support availability on the relationship between body mass index and depressive symptoms

Abstract: OBJECTIVE:To examine relationships between body mass index (BMI) and psychological correlates in Chinese school adolescents during the period of economic transition. DESIGN: Baseline data of 1655 Chinese adolescents aged 11-15 y were retrieved from a longitudinal smoking cessation and health promotion program in Wuhan, China. Assessments of body weight and height, depressive symptoms, perceived peer isolation (PPI) and perceived availability of social support (PASS) were collected. RESULTS: Based on the Intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 50 publications
4
35
0
3
Order By: Relevance
“…Given the fact that obesity is viewed as a non-desirable and stigmatizing characteristic in the American culture, and that many youth are preoccupied with cultural expectations of a slim body as the standard of beauty, being obese has been assumed to predispose youth to depressive symptoms (Merikangas et al, 2012; Roberts, 2000; Sanchez-Villegas et al, 2012; Ting et al, 2012), social isolation (Strauss and Pollack, 2003; Xie, 2005), low self-esteem (Lau et al, 2004), poor health-related quality of life (Pinhas-Hamiel et al, 2006; Tyler et al, 2007), and psychosocial adjustment problems(Erermis et al, 2004). With the development of cognitive functioning during adolescence, the process of self-appraisal and social comparison of body image and physical attractiveness is presumed more operative and relevant to psychosocial adjustment problems among adolescents than among children (Bradley et al, 2008; Harter, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Given the fact that obesity is viewed as a non-desirable and stigmatizing characteristic in the American culture, and that many youth are preoccupied with cultural expectations of a slim body as the standard of beauty, being obese has been assumed to predispose youth to depressive symptoms (Merikangas et al, 2012; Roberts, 2000; Sanchez-Villegas et al, 2012; Ting et al, 2012), social isolation (Strauss and Pollack, 2003; Xie, 2005), low self-esteem (Lau et al, 2004), poor health-related quality of life (Pinhas-Hamiel et al, 2006; Tyler et al, 2007), and psychosocial adjustment problems(Erermis et al, 2004). With the development of cognitive functioning during adolescence, the process of self-appraisal and social comparison of body image and physical attractiveness is presumed more operative and relevant to psychosocial adjustment problems among adolescents than among children (Bradley et al, 2008; Harter, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Pediatric overweight has been associated with depression and anxiety;1 peer isolation and discrimination;2,3 low self-esteem,4 self-concept,5 and social cooperation skills;6 family disharmony;7 dislike of school or trouble with teachers;7 and poor health-related quality of life 8. The underlying mechanisms have been presumably related to the reflected self-appraisal hypothesis and social comparison theory,9-11 which mainly involve cultural norms and social desirability of ideal weight and the process of self-appraisal and social comparison of body image and physical attractiveness.…”
mentioning
confidence: 99%
“…A mediation-moderation approach has been recommended to investigate this association between overweight and depressive symptoms with application of a prospective longitudinal design 3,17. One potential mediator of this association is body image dissatisfaction.…”
mentioning
confidence: 99%
“…In Beck’s study, mediation analysis indicated that pain influenced fatigue directly as well as indirectly by its effect on sleep (Beck et al 2005). Recently in a cross- sectional study, Xie et al demonstrated an association between BMI and depression mediated by perceived peer isolation in adolescents (Xie et al 2005). Small sample size is another limitation in our study.…”
Section: Discussionmentioning
confidence: 99%